Ներաշխարհը միստիկական անուրջներում.Ինտրա - Աիդա Մարտիրոսյան (ՀՀ ԳԱԱ հրատ.)
В основе художественного мышления Чракяна лежит раскрытие философии Души в материальном и духовном мире человека. В произведении “Внутренний мир” Чракян пытается проникнуть и достичь источников предметов, зрительными и голосовыми ощущениями он смешивается с “Воздушной массой”, переходит от видимого, осязательного тела к его душе, которая наполнена всемирным ощущением и с неизменным восторгом стремится к Богу.In the core of the physical and spiritual world of Diran Chrakyan, Intra’s creative thinking is the revelation of the soul's philosophy and the absolute gist of the attainment of the divulgence of Beauty. Chrakyan, in the ''Inner World'' tries to perceive and reach the provenance of things. He, with his visual and vocal senses merges into the ''ethereal leverage''. He proceeds from the visible, touchable, figure and transcends whereas the soul, filled with consciousness of cosmic dimensions, unwavering and with genuine delight yearns for God.
Keywords: Language and Literature